MEFV gene variants in children with Henoch-Schönlein purpura and association with clinical manifestations: a single-center Mediterranean experience. Issue 1 (2nd January 2019) - Ekinci, Rabia Miray Kisla; Balci, Sibel; Bisgin, Atil; Atmis, Bahriye; Dogruel, Dilek; Altintas, Derya Ufuk; Yilmaz, Mustafa
ABSTRACT: Objectives : Henoch-Schönlein purpura (HSP) is characterized by non-thrombocytopenic palpable purpura, abdominal pain, and arthralgia/arthritis. We aimed to describe the clinical presentations of children with HSP in a single center and compare the prevalence of each manifestations between patients with MEFV variants, particularly in exon 10 and those without. Methods : This cohort retrospectively included 144 HSP (59 females, 85 males) patients without Familial Mediterranean Fever (FMF) symptoms and followed for at least 6 months. We utilized the MEFV gene sequencing by using next-generation sequencing platform (MiSeq System, Illumina). Results : At least one MEFV variant was detected in 73 (50.7%) of 144 HSP patients and 5 (3.5%) patients were homozygote for M694V mutation. Although severe gastrointestinal involvement and nephritis rates were similar, we found that serum IgA, leukocyte, and platelet count at diagnosis were higher and hemoglobin was lower in HSP patients with MEFV gene variants in exon 10 than those without. Additionally, HSP patients with MEFV variants in exon 10 more often present with abdominal pain and intussusception. Conclusion : MEFV variants in exon 10 may affect clinical presentation of HSP in populations where FMF is common. While HSP may be an initial symptom of FMF, we speculate that physicians should be aware of FMF possibility in children with intussusception and lower hemoglobin, higher serum IgA, leukocyte, and platelet count.